A Meta-Analysis of Transdiagnostic Cognitive Behavioural Therapy in the Treatment of Child and Young Person Anxiety Disorders. Issue 5 (September 2015) - Ewing, Donna L.; Monsen, Jeremy J.; Thompson, Ellen J.; Cartwright-Hatton, Sam; Field, Andy
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Previous meta-analyses of cognitive-behavioural therapy (CBT) for children and young people with anxiety disorders have not considered the efficacy of transdiagnostic CBT for the remission of childhood anxiety. Aim: To provide a meta-analysis on the efficacy of transdiagnostic CBT for children and young people with anxiety disorders. Methods: The analysis included randomized controlled trials using transdiagnostic CBT for children and young people formally diagnosed with an anxiety disorder. An electronic search was conducted using the following databases: ASSIA, Cochrane Controlled Trials Register, Current Controlled Trials, Medline, PsycArticles, PsychInfo, and Web of Knowledge. The search terms included "anxiety disorder(s)", "anxi*", "cognitive behavio*, "CBT", "child*", "children", "paediatric", "adolescent(s)", "adolescence", "youth" and "young pe*". The studies identified from this search were screened against the inclusion and exclusion criteria, and 20 studies were identified as appropriate for inclusion in the current meta-analysis. Pre- and posttreatment (or control period) data were used for analysis. Results: Findings indicated significantly greater odds of anxiety remission from pre- to posttreatment for those engaged in the transdiagnostic CBT intervention compared with those in the control group, with children in the treatment condition 9.15 times more likely to recover from their anxiety diagnosis than children in the control group. Risk of bias was not correlated with study effect sizes. Conclusions: Transdiagnostic CBT seems effective in reducing symptoms of anxiety in children and young people. Further research is required to investigate the efficacy of CBT for children under the age of 6.